A randomised controlled trial of high versus low long chain triglyceride whole protein feed in active Crohn's disease. Issue 6 (1st December 2001) - Leiper, K; Woolner, J; Mullan, M M C; Parker, T; van der Vliet, M; Fear, S; Rhodes, J M; Hunter, J O
Abstract : BACKGROUND: Polymeric feeds have shown variable efficacy in active Crohn's disease (CD) with remission rates from 36% to 82%. Meta-analyses of elemental, peptide, and whole protein feeds have shown a strong negative correlation between remission rate in CD and the long chain triglyceride (LCT) content of the feed. We performed a randomised controlled double blind trial in patients with active CD comparing two single whole protein feeds with LCT supplying 5% or 30% of the total energy. METHODS: Fifty four patients with active CD (Crohn's disease activity index (CDAI) >200, serum C reactive protein (CRP) 10 mg/l) were randomised to a high or low LCT feed for three weeks. The total amount of energy supplied by fat was identical in the two feeds. Remission was defined as a CDAI ⩽150 and response as a fall in CDAI of ⩾70 or a CRP <10 mg/l. RESULTS: Overall remission rate by intention to treat was 26% for the low LCT feed and 33% for the high LCT feed (p=0.38). Response was achieved in 33% with the low LCT and in 52% with the high LCT feed (p=0.27). CRP <10 mg/l was achieved in 30% in the low LCT and 33% in the high LCT group (p=0.99). Thirty nine per cent (21/54) of patients withdrew before three weeks because of inability to tolerate the diet. Excluding patients unable to tolerate the diet, remission rates were 46% for low LCT and 45% for high LCT (p=0.99). DISCUSSION: This trial has shown no difference in the effect of low and high LCT whole protein feeds in active CD. The previously reported correlation between LCT content of diet and response in active CD is unlikely to be due to LCT itself and may be due to some other component of high LCT feeds.